Agro machine / Fatin Nor Najwa Che Razak … [et al.] - Che Razak, Fatin Nor Najwa; Sia, Grace Merat; Mohd Bakri, Muhammad Syazdie; Zaidi, Siti Nurfatihah; Meor Shuhil, Wan Ain Najma; Hasbullah, Nornajihah Nadia (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
Agriculture is the world's largest industry. It employs more than one billion people and generates over $1.3 trillion dollars' worth of food annually. When agricultural operations are sustainably managed, they can preserve and restore critical habitats, help protect watersheds and improve soil health and water quality. But unsustainable practices have serious impacts on people and the environment. The need for sustainable resource management is increasingly urgent. To shed the light on this aforementioned issue, the researchers come out with the idea to create an innovative vending machine to cut the plastic waste. At the same time, this vending machine sell the organic coco peat modified in small size and a few planting sections. This organic fertilizer is truly biodegradable with a life span up to 3-4 years. Approximately, the use of vending machines is one of the innovative elements, high technology and eco green. Notably, this innovation it able to boost up the activities of small urban farming at the city's areas, apply green elements in their indoor or outdoor. Encouraging the culture of urban farming in apartment. In sum, this innovation is truly supporting 17 SDG goals and have a high potential to be commercialize in a global.